Profitability and leverage on tax avoidance with company size as moderation in IDX manufacturing companies - Maulani, Dzikrilla Sarla; Hidayat, Rendra Arief (MID Publisher International, 2024)
This study investigates the impact of profitability and leverage on tax avoidance, with company size acting as a moderating variable. Utilizing a quantitative approach, the research focuses on tax avoidance as the dependent variable. The sample comprises 17 companies from the textile and garment sector listed on the Indonesia Stock Exchange, covering the period from 2018 to 2022. Purposive sampling was employed to select these companies based on specific criteria. Data analysis was conducted using Multiple Linear Regression and Moderated Regression Analysis (MRA). The results reveal that profitability positively influences tax avoidance, while leverage does not significantly affect tax avoidance. Furthermore, company size enhances the relationship between profitability and tax avoidance but does not significantly impact the relationship between leverage and tax avoidance.